Incidence and determinants of households’ catastrophic payments for TB care: evidence from a multi-country trial (EXIT-TB project) implemented in East Africa - Getnet Yimer; Blandina T Mmbaga; Sayoki Mfinanga; Peter Binyaruka; Bruce J Kirenga; Esther Ngadaya; Godfather Kimaro; Amani Thomas Mori; Francis Donard Ngadaya; Doreen Philbert; Amani Wilfred; Johnson Jeremia Mshiu; et al. (BMJ Public Health)
Background Despite free tuberculosis (TB) services in low-resource settings which are provided under countries’ respective National TB programmes, TB patients incur substantial costs when seeking care. These costs not only act as a barrier to access but also reduce adherence to TB treatment which further affects patients’ health outcomes and poses a financial burden to households. In the context of the EXIT-TB project implementation, we nested a patient cost study aiming at estimating the costs incurred by patients when seeking TB services. In addition, we also assessed the incidence and determinants of catastrophic health expenditure (CHE) among households affected by TB.Methods A cross-sectional analytical study was carried out in four East African Countries, namely; Tanzania, Kenya, Uganda and Ethiopia alongside EXIT-TB project implementation from 2019 to 2022. Direct and indirect costs incurred by drug-sensitive TB patients were collected after they had received TB services. Costs were considered catastrophic if they exceeded 20% of annual household income. Cost data were collected in each country’s national currency and converted to 2023 US dollars afterwards.Results The mean total cost incurred by patients when seeking TB care were US$130.85, US$97.90, US$84.63 and US$101.60 in Tanzania, Kenya, Uganda and Ethiopia, respectively. Overall, more than half (51.81%) of the TB-affected households experienced CHE due to TB. CHE was high among TB-affected households with poor socioeconomic status. TB patients residing in Ethiopia, households with >5 members, households with TB patients as household heads, unemployed and poor socioeconomic status were among the factors associated with a high incidence of CHE (p<0.05).Conclusion Despite the availability of free TB services in East Africa provided by the respective National TB programmes, more than half of TB-affected households experienced CHE due to TB. Our findings reinforce the need for cost mitigation policies among TB-affected households, particularly the worse offs so as to reduce the incidence of CHE and further impoverishment.